Inhibition and kinetic studies of cellulose - and hemicellulose - degrading enzymes of Ganoderma boninense by naturally occurring phenolic compounds - A., Surendran; Y., Siddiqui; N. S., Ali; S., Manickam (Wiley, 2018)
AIM: Ganoderma sp, the causal pathogen of the basal stem rot (BSR) disease of oil palm, secretes extracellular hydrolytic enzymes. These play an important role in the pathogenesis of BSR by nourishing the pathogen through the digestion of cellulose and hemicellulose of the host tissue. Active suppression of hydrolytic enzymes secreted by Ganoderma boninense by various naturally occurring phenolic compounds and estimation of their efficacy on pathogen suppression is focused in this study.